Hot deformation behavior and processing maps of 9Cr3W3Co oxide dispersion-strengthened steel - Yang Wen-Sheng; Wang Jia-Wei; Jiang Lei; Wang Tian-Jian; Pei Yu-Bing (High Temperature Materials and Processes, 2021)
The hot deformation behavior of as-cast 9Cr3W3Co oxide dispersion-strengthened (ODS) steel was investigated by Gleeble 3500 facility in the temperature range of 900–1,150℃ and at strain rates range of 0.01–10 s−1. The constitutive equation and processing maps were established to describe this complex hot deformation process. The true stress–strain curves showed that the softening effects of dynamic recovery and dynamic recrystallization are stronger than the effect of work hardening with further increasing the temperature and strain. The optimal hot working parameters of 9Cr3W3Co-ODS steel are suggested to be T = 1,050–1,100°C and ε̇\dot{ε } = 0.03–0.3 s−1.